QO’LQANOTLI SUT EMIZUVCHILAR (CHIROPTERA) FAUNASINI MUHOFAZA QILISHNING AYRIM JIHATLARI - Abduraxmanova O.Sh, Abduraxmanova O.Sh; Rajabov F.H., Rajabov F.H.; Kuchboyev , Abdiraxim (Actual problems and prospects of the study of the fauna, 2024)
This article provides information on some aspects of the study, study and conservation of the fauna of the order mammalian arthropods, bats (Chiroptera).